The mechanism of stem cell differentiation into smooth muscle cells - Xiao, Qingzhong; Wang, Gang; Luo, Zhenling; Xu, Qingbo (Thrombosis and Haemostasis, 2010)
Stem cells represent one of the most promising areas in biological and medical research. All stem cells are defined as having two basic properties: unlimited self-renewal and the broad potential to differentiate in vitro, via ″progenitor cells″, into somatic cells of many tissue types, in which smooth muscle cell (SMC) differentiation is a complicated and not well defined process. It is known that serum response factors (SRF) and co-activator myocardin are essential transcription factors in SMC differentiation. Upstream activators or regulators for the transcription factors have been recently identified, such as reactive oxygen species, histone deacetylases, microRNAs and extracellular matrix (ECM) proteins and integrins. In this review we, therefore, aim to briefly summarise recent progress in the mechanism of stem cell differentiation into SMCs to highlight the potential targets for promoting/inhibiting SMC differentiation useful for vessel-tissue engineering and treatment of vascular disease.
Keywords: Stem cells; smooth muscle cells; differentiation; vascular disease